The Effect of Internal Control Effectiveness, Accountability, and Transparency on Corporate Financial Reporting Quality: The Moderating Role of Human Resource Competence - Meifanny Azri Shafira; Erlina Erlina; Fahmi Natigor Nasution (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the effect of internal control effectiveness, accountability, and transparency on the quality of corporate financial reporting, with human resource competence as a moderating variable at PT Pelindo Multi Terminal. The research employs a quantitative descriptive method. The study population consists of 90 individuals, including directors, internal control systems, audit committee members, corporate secretariat, and the finance division, determined using a saturated sampling technique. Primary data were collected through questionnaires utilizing a Likert scale, and the data were analyzed using SmartPLS 4.0 software. The findings indicate that internal control effectiveness, accountability, and transparency have a positive and significant effect on the quality of corporate financial reporting. However, the moderation test results show that human resource competence is only able to moderate the relationship between internal control effectiveness and accountability on financial reporting quality. In contrast, for transparency, the moderation test demonstrates no significant effect, as it does not strengthen the relationship between transparency and financial reporting quality. These findings are expected to provide valuable insights for PT Pelindo Multi Terminal in achieving high-quality financial reporting.